The Role of Fishery Extensions in Improving Quality Catfish Farmers in Binjai City North Sumatra Province - Nasution, Muhammad Nur (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Abstract: This research aims to investigate and analyze the role of fisheries extension officers in improving the quality of catfish farmers in Binjai City, North Sumatra Province. The quality of catfish farmers is understood as a combination of technical knowledge, practical skills, business management, and the level of innovation acceptance that affects the productivity and sustainability of catfish farming. The research methodology involves field surveys, interviews, and secondary data analysis to understand the conditions of catfish farmers and the effectiveness of the role of fisheries extension officers. The data will be analyzed qualitatively and quantitatively to obtain a holistic picture of the contribution of fisheries extension officers to the improvement of catfish farmer quality. The results of the research are expected to provide in-depth insights into specific aspects that need improvement by fisheries extension officers, such as increasing technical knowledge, implementing more efficient aquaculture practices, and better business management. The implications of this research can be used as a basis for improving fisheries extension programs and sustainable development strategies for catfish farmers in Binjai City and surrounding areas. This research is expected to contribute to the knowledge literature on the role of fisheries extension officers in the context of fisheries management and the empowerment of fishing community